Decreased levels of γ-aminobutyric acid in temporal lobe of children with 47, XYY syndrome. Issue 7 (5th May 2021) - Roberts, Timothy P.L.; Bloy, Luke; Miller, Judith S.; Blaskey, Lisa; Ross, Judith
Abstract : Background: 47, XYY syndrome (XYY) is a male sex chromosome disorder where subjects have one X chromosome and two copies of the Y chromosome. XYY is associated with a physical phenotype and carries increased risk of neurodevelopmental disorders such as autism spectrum disorder (ASD). Imbalance of excitation and inhibition has been proposed as a putative biological basis of disorders such as ASD [1–3 ] and several studies have reported atypical brain γ-aminobutyric acid (GABA) levels in this population. Given the male preponderance in the prevalence of ASD, the unique presence of the Y chromosome in males leads to the intriguing possibility of investigating boys with XYY syndrome as a model of excess Y-chromosome genes. Method: In this study, we investigated the associations of genotype and clinical phenotype with levels of GABA, estimated by regionally localized edited magnetic resonance spectroscopy in boys with 47, XYY syndrome compared to age-matched typically developing (XY) peers. Results: Overall, we observed a decrease in GABA levels in XYY vs. XY, which appeared more significant in the left compared to the right hemisphere. There was no additional significant modulation of GABA levels in XYY according to presence/absence of ASD diagnosis. Interestingly, a positive correlation between bilateral GABA levels and testosterone levels was observed in pubescent XY boys that was not observed in XYY. Conclusion: The inhibitory neurotransmitter GABA appears to be reduced in boys with 47, XYY, especially in the left hemisphere. Further, the typical association between GABA and testosterone levels, observed in older typically developing control boys was not evident in boys with 47, XYY.